Find the general solution of the homogeneous system below. Give your answer as a vector.
x1 + 2x2 - 3x3 = 0
4x1 + 7x2 - 9x3 = 0
-x1 - 3x2 + 6x3 = 0

Respuesta :

Answer:

Step-by-step explanation:

Given the system of homogeneous equations

x1 + 2x2 - 3x3 = 0  ................. 1

4x1 + 7x2 - 9x3 = 0 ................... 2

-x1 - 3x2 + 6x3 = 0..................... 3

First we will reduce the equation to two equations and two unknowns;

add equation 1 and 3;

2x2-3x2 +(-3x3+6x3) = 0

-x2 + 3x3 = 0

x2 = 3x3 .......... 4

Multiply equation 3 by 4 and add to equation 2;

equation 3 * 4 will give;

-4x1 - 12x2 + 24x3 = 0..................... 5

add equation 5 to equation 2;

7x2-12x2-9x3+24x3 = 0

-5x2 - 15x3 = 0 .......... 6

5x2 = 15x3

x2 = 3x3

Let x2 = k

From equation 4;

k = 3x3

x3 = k/3

substitute x2 = k and x3 = k/3 into equation 1 to get x1 in terms of k

From 1, x1 + 2x2 - 3x3 = 0

x1+2k-3(k/3) = 0

x1 +2k-k = 0

x1 +k = 0

x1 = -k

Writing the answer in vector form will give (x1. x2. x3) = (-k, k, k/3)

k(-1, 1, 1/3)

Hence the answer to the system of equation in vector form is k(-1, 1, 1/3) where k is any constant.